Commentary: does immune suppression increase risk of developing acute myeloid leukemia? - Gale, Robert Peter; Opelz, Gerhard (Leukemia, 2012)
Risk of developing some cancers is markedly increased in settings of immune suppression including after solid organ transplants and in persons with inherited immune-deficiency disorders and those with HIV-1 infection. These cancers include lymphomas, melanoma and non-melanoma skin cancers, kidney and cervical cancers, Kaposi sarcoma and neuroblastoma. There are no reports of an increased acute myeloid leukemia (AML) in settings of immune suppression. This is curious because some data suggest the immune suppression may be important in increasing AML risk in experimental settings, and that immune stimulation may be useful in treating AML. To see whether immune suppression is correlated with an increased risk of developing AML, we analyzed data from 248224 recipients of kidney (N=217219) and heart (N=31005) transplants. Among the kidney transplant recipients, the standardized incidence ratio (SIR) for developing AML was 1.90 (95% confidence interval, 1.4-2.4; P<0.001). Among the heart transplant recipients, the SIR was 5.1 (3.4-7.1; P<0.001). These data suggest immune suppression increases risk of developing AML and that this risk is even higher, following intense prolonged immune suppression. Implications for AML development and therapy are discussed.
Published online 26 August 2011
Gesehen am 12.06.2018